Novelty in limbal stem cell culture and cell senescence. (April 2019) - Boroumand, Nadia; Nosrati Tirkani, Abolfazl; Javid, Dina; Hasani, Ali; Taherzadeh, Danial; Hosseinzadeh, Alireza; Nooripour, Sanaz; Zarei-Ghanavati, Siamak; Hashemy, Seyed Isaac; Alamdari, Daryoush Hamidi
Abstract: Limbal stem cell deficiency is a pathological state. Recently, limbal stem cell (LSC) transplantation has attracted great interest as a therapeutic method which mainly involves in-vitro expansion of LSCs. It is believed that ex-vivo cultivation conditions could affect the outcome of surgery and the rate of successful transplantation. Thus, we aimed to define a suitable culture condition by conducting a research on ex-vivo expanded LSCs to maintain an optimized graft of amniotic membrane with cultivated-limbal stem cells, regarding the quantity and quality, with the hope of improving the clinical outcome. Highlights: Fibrin glue enriched with PRP and growth factors creates 3D scaffold and increases NP63+ cells' number from 3% to around 6%. PRP-fibrin glue attaches the explant on amniotic membrane for 14 days in culture condition without any sign of degradation. Media supplement with N-acetyl cysteine decreases β-galactosidase activity during ex-vivo cell culture.